Morphology, Activation, and Metal Substitution Effects of AlPO4-5 for CO2 Pressure Swing Adsorption - Papageorgiou, Andreas; Reddy, K. Suresh Kumar; Karonis, Dimitrios; Reinalda, Donald; Al Wahedi, Yasser; Karanikolos, Georgios N. (Frontiers in Chemistry, 2020)
Aluminophosphate AlPO4-5, an AFI zeotype framework consisting of one-dimensional parallel micropores, and metal-substituted AlPO4-5 were prepared and studied for CO2 adsorption. Preparation of AlPO4-5 by using different activation methods (calcination and pyrolysis), incorporation of different metals/ions (Fe, Mg, Co, and Si) into the framework using various concentrations, and manipulation of the reaction mixture dilution rate and resulting crystal morphology were examined in relation to the CO2 adsorption performance. Among the various metal-substituted analogues, FeAPO-5 was found to exhibit the highest CO2 capacity at all pressures tested (up to 4 bar). Among the Fe-substituted samples, xFeAPO-5, with x being the Fe/Al2O3 molar ratio in the synthesis mixture (range of 2.5:100 to 10:100), 5FeAPO-5 exhibited the highest capacity (1.8 mmol/g at 4 bar, 25 °C) with an isosteric heat of adsorption of 23 kJ/mol for 0.08 to 0.36 mmol/g of CO2 loading. This sample also contained the minimum portion of extra-framework or clustered iron and the highest mesoporosity. Low water content in the synthesis gel led to the formation of spherical agglomerates of small 2D-like crystallites that exhibited higher adsorption capacity compared to columnar-like crystals produced by employing more dilute mixures. CO2 adsorption kinetics was found to follow a pseudo-first order model. The robust nature of AlPO4-5 - based adsorbents, their unique one-dimensional pore configuration, fast kinetics, and low heat of adsorption make them promising for pressure swing adsorption of CO2 at industrial scale.